Well-being in children and adolescents with hearing/listening impairment from a special needs school during the Covid-19 pandemic: associations with stressful situations and self-efficacy - Vera Gillé; Kathrin Allgayer; Melanie Wengert; Heike Eschenbeck (Health Psychology and Behavioral Medicine)
Background: Research on the implications of the COVID-19 pandemic and its impact on well-being among children with disabilities is scarce. Studies in children and adolescents that have problems with hearing or listening, a possibly particularly vulnerable group during the pandemic, are largely lacking.Aims: We investigated well-being, stress experiences, and self-efficacy among children who are deaf or hard of hearing (D/HH) or with auditory processing disorder (APD) during the COVID-19 pandemic.Methods: A total of N = 90 children who are D/HH or with APD (47% girls, Mage = 14.95, SD = 2.02) from a special needs school completed self-reports. Data were assessed in Germany in May 2021.Results: Over half the children (52%) reported low well-being. Well-being correlated negatively with stress (perceived stress and stressor occurrence, both for the three different domains: general everyday stressors, pandemic-specific stressors, hearing-specific stressors, r = −.27 to −.56) and positively with self-efficacy (r = .42). Regression analyses confirmed the positive association between well-being and self-efficacy (β = .37/.30). Regarding stress, perceived stress for pandemic-specific stressors (e.g. homeschooling, crowds, β = -.35) and a stronger occurrence of everyday stressors (e.g. gossiping, parents having no time, β = -.45) were relevant for lower well-being.Conclusions: Especially everyday and pandemic-related stressors should be taken seriously. Self-efficacy should be strenghtened as a resource.